Hubungan Pengetahuan Ibu dengan Kemampuan Deteksi Dini Tumbuh Kembang Bayi 0 – 12 Bulan di Posyandu Anyeler 5 Desa Jarin Kecamatan Pademawu - Ratna Indriyani; Sari Pratiwi Apidianti (Universitas Islam Madura, 2022)
The prevalence of malnutrition in Indonesia is still high compared to neighboring countries, the cause is the quantity and quality of food intake which can be judged from its consumption in terms of quality and diversity. This study aims to determine the relationship between mother's knowledge and the ability to detect early growth and development of children 0-12 months at the Anyelir 5 Posyandu, Jarin Village. This research method uses correlational analysis. The population is the total number of mothers of infants 0 -12 months in the Anyelir 5 Posyandu in Jarin Village as many as 72 people. The sample in this study were 61 mothers with babies 0-12 months. It is expected that health workers need to provide counseling to mothers about good weaning methods, appropriate weaning times and good weaning foods, analysis using Spearman Rank Correlation test obtained rho count value (0.00) < 0.05, where Ha is accepted which means there is The relationship between mother's knowledge and the ability to detect early growth and development of infants 0-12 months at the Anyelir 5 Posyandu, Jarin Village, Pademawu District, Pamekasan Regency in 2012.